Concurrent activation of OsAMT1;2 and OsGOGAT1 in rice leads to enhanced nitrogen use efficiency under nitrogen limitation. (27th May 2020) - Lee, Sichul; Marmagne, Anne; Park, Joonheum; Fabien, Chardon; Yim, Yehyun; Kim, Sun‐ji; Kim, Tae‐Heon; Lim, Pyung Ok; Masclaux‐Daubresse, Celine; Nam, Hong Gil
Summary: Nitrogen (N) is a major factor for plant development and productivity. However, the application of nitrogenous fertilizers generates environmental and economic problems. To cope with the increasing global food demand, the development of rice varieties with high nitrogen use efficiency (NUE) is indispensable for reducing environmental issues and achieving sustainable agriculture. Here, we report that the concomitant activation of the rice ( Oryza sativa ) Ammonium transporter 1;2 ( OsAMT1;2 ) and Glutamate synthetase 1 (OsGOGAT1) genes leads to increased tolerance to nitrogen limitation and to better ammonium uptake and N remobilization at the whole plant level. We show that the double activation of OsAMT1;2 and OsGOGAT1 increases plant performance in agriculture, providing better N grain filling without yield penalty under paddy field conditions, as well as better grain yield and N content when plants are grown under N llimitations in field conditions. Combining OsAMT1;2 and OsGOGAT1 activation provides a good breeding strategy for improving plant growth, nitrogen use efficiency and grain productivity, especially under nitrogen limitation, through the enhancement of both nitrogen uptake and assimilation. Significance Statement: We report that concurrent activation of OsAMT1;2 and OsGOGAT1 confers better growth and improves the grain yield and quality of rice, especially under nitrogen limitation. Thus, our approach constitutes a promising strategy for improving nitrogen use efficiency in rice.